The Semantics Relationship of Noun and Verb Pairs in Tai Phuan: ความสัมพันธ์ทางความหมายของคู่คำนาม-กริยาในภาษาไทพวน - Aree, Usana (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2022)
In this research, the common properties of the categories of Tai Phuan words, which are both nouns and verbs from the Tai Phuan dictionary are investigated to analyze the semantic relationship of noun-verb pairs. The concept of categorization according to the prototype theory was used. The research results show that the vocabulary of noun-verb pairs from Tai Phuan dictionary consists of 73 words. They were divided into 2 groups: 1) noun-verb pairs that have no semantic properties are related to each other and include a total of 47 words, accounting for 64.38%. 2) noun-verb pairs that have semantic properties are related, totaling 26 words, which corresponds to 36.62%. Divided into words with relative semantic properties, 7 words. Partially related semantic terms, 14 words. Moreover, a group of lexical pairs that have no semantic properties but are related, 5 words. It can be analyzed that there are 23 prototypical verbs and 3 prototypical nouns. บทคัดย่อ งานวิจัยนี้เป็นการศึกษาคุณสมบัติร่วมของหมวดหมู่ของคำศัพท์ภาษาไทพวนที่ทำหน้าที่เป็นทั้งคำนามและคำกริยาจากพจนานุกรมภาษาไทพวน ฉบับเฉลิมฉลอง 90 ปี มหาวิทยาลัยราชภัฏเชียงใหม่ พุทธศักราช 2557 เพื่อวิเคราะห์ความเชื่อมโยงทางความหมายของคู่คำนาม-กริยา โดยใช้กรอบแนวคิดเรื่องการจัดประเภท (categorization) ตามทฤษฎีต้นแบบ (prototype theory) ผลการศึกษาพบว่าคำศัพท์ที่เป็นคู่คำนาม-กริยาจากพจนานุกรมภาษาไทพวนมีจำนวนทั้งสิ้น 73 คำ พบกลุ่มคำพ้องที่ไม่ปรากฏคุณสมบัติร่วมของหมวดหมู่ระหว่างคำนามและคำกริยา จำนวน 47 คำ คิดเป็นร้อยละ 64.38 และพบกลุ่มที่ปรากฏคุณสมบัติร่วมของหมวดหมู่ระหว่างคำนามและคำกริยา จำนวน 26 คำ คิดเป็นร้อยละ 36.62 ซึ่งสามารถจำแนกได้เป็นกลุ่มคู่คำศัพท์ที่มีคุณสมบัติทางความหมายร่วมกัน จำนวน 7 คำ กลุ่มคู่คำศัพท์ที่มีคุณสมบัติทางความหมายร่วมกันบางส่วน จำนวน 14 คำ และกลุ่มคู่คำศัพท์ที่ไม่มีคุณสมบัติทางความหมายร่วมกันแต่มีความเชื่อมโยงกัน จำนวน 5 คำ โดยสามารถวิเคราะห์ได้ว่ามีคำกริยาเป็นต้นแบบ จำนวน 23 คำ และมีคำนามเป็นต้นแบบ จำนวน 3 คำ